RELEVANSI RENCANA PEMBELAJARAN DALAM INTERNATIONAL STANDAR ORGANIZATION (ISO) 9001:2008 TERHADAP RENCANA PEMBELAJARAN DALAM STANDAR PROSES SEKOLAH MENENGAH KEJURUAN (SMK) - Setiawan, David Firna (EQUILIBRIA PENDIDIKAN : Jurnal Ilmiah Pendidikan Ekonomi, 2016)
Improving the quality, relevance and standardization in education through ISO 9001: 2008 certification must comply with national education standards. This article aims to analyze the relevance of the implementation lesson plan in the ISO 9001: 2008 standard with the implementation plan of learning in the Constitution Number 20 years 2003 about National Education System, Government Regulation Number 19 years 2005 about National Education Standards, and Government Regulation Number 32 about amendment of Government Regulation Number 19 Year 2005 about National Education Standards. The results of the analysis show that there is no significant difference in lesson plan. So the ISO 9001: 2008 standard is relevant applied in vocational high School.